Education During Pandemic: The Adoption of Learning Resource on Wifi Hub Expanded Electronic Learning in Sarangani (LR on WHEeLs) in Alabel 4 District - Castillas, Glenn M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The purpose of this study is to look into teachers' willingness to use the Learning Resources on Wi-Fi Hub for Expanded e-Learning (LR on WHEeLs) as a flexible learning option to extend the reach of e-learning to remote villages, particularly those outside of the service coverage of major telecommunications companies and internet service providers. This study employs quantitative research, with data collected via an online survey questionnaire. Purposive sampling was also used to select respondents from Alegria National High School. The collected data was statistically analyzed using weighted mean. The teachers' readiness on LR on WHEeLs anchored to the uses of ICT revealed the following: first, the school staff and the department as a whole provide ICT professional development. Second, ICT-based activities and materials for teaching were frequently used, and subsequently, teachers were confident in their ICT skills. This indicates that the majority of teacher-respondents had adapted to so-called 21st-century learners. However, it has been revealed that the difficulties encountered by participants in the use of LR on WHEeLs include a lack of interest on the part of teachers, a lack of benefit from using Technology in teaching and learning, and an absence of adequate content/materials. As a result, proper reinforcement must be provided to teachers through training, orientation, and seminars, as well as the provision of the support needed and materials for the use of LR on WHEeLs.